Sensing properties of gas sensor based on adsorption of NO2 with defect, pristine, Fe and Si-MoS2 layer - Shakil, Shifur Rahman; Khan, Sabbir Ahmed (© 2014 Sumy State University, 2017)
This article was published in the Journal of Nano- and Electronic Physics [© 2014 Sumy State University] and the article website is at: http://jnep.sumdu.edu.ua/en/component/content/full_article/1329